INFLUENCE OF WEATHER CONDITIONS, LAND TYPE AND SOWING DENSITY ON MAIZE PRODUCTIVITY - Živanović, Ljubiša R.; Golijan-Pantović, Jelena; Stojković, Dragan R.; Kolarić, Ljubiša D.; Ikanović, Jela N.; Kolašinac, Stefan M. (Journal of Agricultural Sciences (Belgrade), 2024)
High maize yields can only be achieved on fertile, loose and well-permeable soils. Previous research indicates that novel maize hybrids exhibit favorable responses to higher crop density. The aim of this work was to study the influence of meteorological conditions, soil type and seeding density during the growing season on cob length, number of grain rows on the cob, number of sterile plants, grain yield and grain water content of corn hybrid AS 6E02 (FAO 620). Tests were carried out during 2017 and 2018 through field microexperiments in the agroecological conditions of Vranje municipality using the split-plot design in four repetitions on eutric cambisol, vertisol and alluvium soils. The area of the plot for grain yield was 8.4 m2. The agrotechnics used in the experiment were standard, as for regular corn production. The years in which the surveys were conducted differed in terms of meteorological conditions, amount and distribution of precipitation. The smallest average cob length (17.6 cm) for all investigated soils and years was obtained in the narrow-row sowing. The number of grain rows did not vary significantly depending on the sowing density. In the two-year average, the grain yield was singnificantly higher influenced by the type of soil in relation to the sowing density. On average for soil types and years, the lowest percentage of sterile plants (1.90%) was found at the densest sowing (75,187 seeds ha-1). In comparison to 2017, the water content in 2018 was higher by 8.5 index points.
Keywords: maize, soil, sowing, productivity, seed yield